Setting up of an integrative center for the management of mild-moderate COVID-19 - Tanuja Manoj Nesari; Prasanth Dharmarajan; Arun Kumar Mahapatra; S Rajagopala; Manoj Nesari; Alka Kapoor; Deepak Bhati; Anil Kumar; Sonam Kumari; P S Arshathjyothi; Aparna Dileep (Wolters Kluwer Medknow Publications, 2022)
Introduction: Besides the expansion of vaccine drive, the discovery of new strains of corona virus is creating havoc all around the world. Based on the pragmatic trial conducted, there is an increasing recognition that an effective integrated holistic approach is urgently needed to combat the COVID pandemic. During an infectious outbreak, a health-care unit is anticipated to function as a high-level isolation unit. Herein, we describe the execution plan, experiences, observations, and challenges that were encountered during the establishment and functioning of COVID Health-Care Ward at All India Institute of Ayurveda. Methodology: Since the situation was novel, standard operative procedures and protocols were developed accordingly. Strategic plans carried out in infrastructure, biomedical waste management, surveillance, and observations were compiled directly from the hospital administration. Results: Till date when the 29th team has completed the duty rotation, about 600 COVID mild-to-moderate positive cases have been successfully managed. Zero incidence of nosocomial COVID transmission or death has been reported so far. The recovery speed of patients was found to be remarkably faster at COVID Health Center-AIIA as compared to all other hospitals of the state and a significant number of patients were recovered with the use of Ayurvedic medications alone. On follow-up, only a limited number of patients (two patients) turned up with mild severity of post-COVID complications. Mild respiratory discomfort was noted in these patients for a period of 2 months. The score for Anxiety Depression Scale of among patients and health-care workers reduced significantly. Conclusion: Indigenous system of medicines is comparatively less explored in pandemic times. Here, a tertiary care hospital has upgraded to integrative health-care model in the management of mild-to-moderate COVID-19 cases.